2007
DOI: 10.1159/000098190
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a new repetitive element in the sex chromosomes of <i>Leporinus elongatus</i> (Teleostei: Characiformes: Anostomidae): new insights into the sex chromosomes of <i>Leporinus</i>

Abstract: Leporinuselongatus represents an interesting model for studies on chromosome evolution since it possesses a conspicuous ZZ/ZW sex chromosome system that has been characterized mainly by basic cytogenetic techniques. In the present study we describe a dispersed repetitive element (named LeSpeI) related to the sex chromosomes of L.elongatus. Females revealed clusters of LeSpeI on the long arm of the W chromosome and in the acrocentric NOR-bearing chromosome pair. In males, the signal was restricted to the perice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(84 citation statements)
references
References 48 publications
6
70
0
8
Order By: Relevance
“…Among fish whose genomes have been sequenced, the pufferfish (Takifugu rubripes, order Tetraodontiformes) has a male-heterozygous region (Kikuchi et al 2007). In the zebrafish (Danio rerio, Cypriniformes), sex is determined by a combination of genetic and environmental influences (Siegfried and Nusslein-Volhard 2008), while among its relatives, the goldfish has an XY system of GSD (Zhang and Wu 1985) and Leporinus (Characiformes) has a strongly heteromorphic ZW system, with largely heterochromatic W chromosomes, which have probably undergone W-autosome translocations (Parise-Maltempi et al 2007). …”
Section: Genetic Mapping Of Sex-determining Regionsmentioning
confidence: 99%
“…Among fish whose genomes have been sequenced, the pufferfish (Takifugu rubripes, order Tetraodontiformes) has a male-heterozygous region (Kikuchi et al 2007). In the zebrafish (Danio rerio, Cypriniformes), sex is determined by a combination of genetic and environmental influences (Siegfried and Nusslein-Volhard 2008), while among its relatives, the goldfish has an XY system of GSD (Zhang and Wu 1985) and Leporinus (Characiformes) has a strongly heteromorphic ZW system, with largely heterochromatic W chromosomes, which have probably undergone W-autosome translocations (Parise-Maltempi et al 2007). …”
Section: Genetic Mapping Of Sex-determining Regionsmentioning
confidence: 99%
“…clear correlation between these sequences and sex chromosomes has been established by numerous studies (e.g., Nanda et al 1990Nanda et al , 2000Matsubara et al 2006;Kejnovsky et al 2009) including several Neotropical fish groups (e.g., Parise-Maltempi et al 2007;Cioffi et al 2011Cioffi et al , 2012Machado et al 2011), suggesting that the differentiation of sex chromosomes' mechanism is often associated with the accumulation of repetitive DNA. Accordingly, repetitive sequences represent a powerful tool to elucidate both the processes of morphological differentiation of sex chromosomes in fishes and to possibly understand some of the diversity of the differentiation systems observed in this group of vertebrates (Cioffi et al 2011).…”
Section: Discussionmentioning
confidence: 93%
“…Fishes, however, express all possible forms of sex determination systems somehow associated with the huge biodiversity levels observed among them (reviewed in Volff et al 2007). In the particular case of Neotropical fishes, female heterogamety was reported in Characidium Reinhardt, 1867 and Parodon genera Valenciennes, 1850 (e.g., Vicente et al 2003;Vicari et al 2008;Machado et al 2011), male heterogamety was found in, e.g., Hoplias malabaricus (Bloch, 1794) (Cioffi et al 2011(Cioffi et al , 2012, and other species have multiple sex chromosomes, such as Leporinus elongatus Valenciennes, 1850 (Parise-Maltempi et al 2007) or Harttia carvalhoi Miranda Ribeiro, 1939 (Cioffi et al 2012) among others. Despite the differences in sex chromosome determination, these chromosomes share some features: Y and W are mostly heterochromatic while X and Z usually have more euchromatic regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando que o DNA satélite consiste em repetições em tandem que geralmente estão localizadas em regiões cromossômicas com conhecidas restrições a recombinação, como regiões pericentroméricas (Oliveira e Wright, 1998), regiões adjacentes ao DNAr 5S (Martins et al, 2006), regiões periteloméricas (Saito et al, 2007) e em cromossomos sexuais e B (Reed e Phillips, 1995;Mandrioli et al, 2003;Parise-Maltempi et al, 2007), pode-se supor que a significativa variabilidade cariotípica observada em populações de C. cf. gomesi da bacia do rio Tietê esteja diretamente relacionada a uma elevada taxa de mutação cromossômica principalmente nestas regiões, bem como a alguns aspectos relacionados ao hábito de vida da espécie e à geografia da região da Cuesta de Botucatu, que facilitariam a fixação de populações apresentando novas variantes cromossômicas.…”
Section: Cromossomos Sexuais E Cromossomos Bunclassified